Isolation and Characterization of Six Vibrio parahaemolyticus Lytic Bacteriophages From Seafood Samples - Tan, Chia Wanq; Rukayadi, Yaya; Hasan, Hanan; Abdul-Mutalib, Noor-Azira; Jambari, Nuzul Noorahya; Hara, Hirofumi; Thung, Tze Young; Lee, Epeng; Radu, Son (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus is a foodborne pathogen that is frequently isolated from a variety of seafood. To control this pathogenic Vibrio spp., the implementation of bacteriophages in aquaculture and food industries have shown a promising alternative to antibiotics. In this study, six bacteriophages isolated from the seafood samples demonstrated a narrow host range specificity that infecting only the V. parahaemolyticus strains. Morphological analysis revealed that ɸVp33, ɸVp22, ɸVp21 and ɸVp02 belong to the Podoviridae family, while ɸVp08 and ɸVp11 were categorized into the Siphoviridae family. All bacteriophages were composed of DNA genome and showed distinctive restriction fragment length polymorphism. The optimal MOI for bacteriophage propagation was determined to be 0.001 to 1. One-step growth curve revealed that the latent period ranged from 10 to 20 min, and the burst size of bacteriophage was approximately 17 to 51 PFU/cell. The influence of temperature and pH levels on the stability of bacteriophages showed that all bacteriophages were optimally stable over a wide range of temperatures and pH levels. In vitro lytic activity of all bacteriophages demonstrated to have a significant effect against V. parahaemolyticus. Besides, the application of a bacteriophage cocktail instead of a single bacteriophage suspension was observed to have a better efficiency to control the growth of V. parahaemolyticus. Results from this study provided a basic understanding of the physiological and biological properties of the isolated bacteriophages before it can be readily used as a biocontrol agent against the growth of V. parahaemolyticus.